Flavor Dependent Retention of Remote Food Preference Memory - Singh, Aditya; Kumar, Suraj; Singh, Vikram Pal; Das, Asish; Balaji, J. (Frontiers in Behavioral Neuroscience, 2017)
Social Transfer of Food Preference (STFP) is a single trial non-aversive learning task that is used for testing non-spatial memory. This task relies on an accurate estimate of a change in food preference of the animals following social demonstration of a novel flavor. Conventionally this is done by providing two flavors of powdered food and later estimating the amount of food consumed for each of these flavors in a defined period of time. This is achieved through a careful measurement of leftover food for each of these flavors. However, in mice, only a small (~1 g) amount of food is consumed making the weight estimates error prone and thereby limiting the sensitivity of the paradigm. Using multiplexed video tracking we show that the pattern of consumption can be used as a reliable reporter of memory retention in this task. In our current study, we use this as a measure and show that the preference for the demonstrated flavor significantly increases following demonstration and the retention of this change in preference during remote testing is flavor specific. Further, we report a modified experimental design for performing STFP that allows testing of change in preference among two flavors simultaneously. Using this paradigm we show that during remote testing for thyme and basil demonstrated flavors, only basil demonstrated mice retain the change in preference while thyme demonstrated mice do not.